2023
DOI: 10.14309/ajg.0000000000002557
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Ambulatory Reflux Monitoring Systems for Evaluation of Chronic Laryngeal Symptoms

Amanda J. Krause,
Madeline Greytak,
Alexander M. Kaizer
et al.

Abstract: INTRODUCTION: Among patients with chronic laryngeal symptoms, ambulatory reflux monitoring off acid suppression is recommended to evaluate for laryngopharyngeal reflux (LPR). However, reflux monitoring systems are diverse in configuration and monitoring capabilities, which present a challenge in creating a diagnostic reference standard in these patients. This study aimed to compare diagnostic yield and performance between reflux monitoring systems in patients with chronic laryngeal symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The clinical diagnosis of LPR is challenging regarding the non-specificity of symptoms and signs and the low therapeutic success rate of empirical treatment [15][16][17][18][19]. HEMII-pH is considered as the most reliable tool, but this approach remains expensive and poorly tolerated by patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis of LPR is challenging regarding the non-specificity of symptoms and signs and the low therapeutic success rate of empirical treatment [15][16][17][18][19]. HEMII-pH is considered as the most reliable tool, but this approach remains expensive and poorly tolerated by patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published multicentre study of 813 patients with chronic laryngeal symptoms, investigators identified higher diagnostic yield of pathological GERD on prolonged wireless pH monitoring compared to 24 h impedance-pH, even when taking into account non-acidic and weakly acidic reflux events identified on impedance-pH monitoring. 50 Another complicating factor is that the presence of conclusive GERD on reflux monitoring does not necessarily attribute GERD as the aetiology of symptoms. 12 Overall, ambulatory reflux monitoring is a key diagnostic test in evaluating patients with LPR.…”
Section: Risk Factor Modelling and Phenotypingmentioning
confidence: 99%
“…The choice of reflux testing for LPR may, therefore, entail balancing between prolonged monitoring to increase sensitivity (wireless pH), shorter study with additional nonacidic information (catheter-based MII-pH), and pharyngeal-focused monitoring with less standardized distal data (HEMII-pH). In a recent multicenter international study, wireless pH monitoring outperformed MII-pH and HEMII-pH in identifying abnormal reflux in patients with chronic laryngeal symptoms [25 ▪ ]. However, the definition for abnormal reflux utilized in the study was based on criteria from the Lyon consensus [26], which was established for typical reflux symptoms with focus on acid reflux, rather than specifically for EER.…”
Section: Introductionmentioning
confidence: 99%